PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN DENGAN KEMAMPUAN KERJA SEBAGAI VARIABEL MEDIASI (Studi Pada PT Bank Pembangunan Daerah Jawa Timur Tbk Cabang Pamekasan) - Rani Nur Fitrianti; Chamariyah Chamariyah (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This study aims to analyze the influence of organizational culture and compensation on employee performance with work ability as a mediating variable at PT BPD Jawa Timur Tbk Pamekasan branch. This type of research is associative with quantitative approach. Organizational culture has a significant effect on improving employee performance at PT. East Java Regional Development Bank Tbk Pamekasan Branch. Compensation has a significant effect in helping improve employee performance at PT. East Java Regional Development Bank Tbk Pamekasan Branch. Organizational culture has a significant effect on improving work skills at PT. East Java Regional Development Bank Tbk Pamekasan Branch. 4) Compensation has a significant effect on improving work ability at PT. East Java Regional Development Bank Tbk Pamekasan Branch. Work ability has a significant negative effect on improving employee performance at PT. East Java Regional Development Bank Tbk Pamekasan Branch. Organizational culture has a significant negative effect on increasing work ability and work performance of employees of PT. East Java Regional Development Bank Tbk Pamekasan Branch. Compensation has a significant negative effect on increasing work ability and work performance of employees of PT. East Java Regional Development Bank Tbk Pamekasan Branch.